Finding Circulation using Zhukovsky’s Theorem - Isgandarov, M.G.; Nusratzade, M.I. (Herald of Azerbaijan Engineering Academy, 2024)
In the presented article, it was proved that the lifting force of an infinitely extendable wing is equal to the product of gas (liquid) density, speed, circulation the length of the wing section. It is shown that the direction of influence of the lifting force is obtained by turning the direction of the velocity of the flow by 90 degrees against the direction of circulation. With the help of Zhukovsky’s theorem, it was shown that the connection between the circulation and the aerodynamic parameters of the wing is established.